Enhancing physical, mechanical, tribological and contact characteristics of water-based lubrication using ceramic nanomaterials MgO and SiC for metal-to-metal sliding interfaces - Leong, Ming Rui; Sulaiman, Mohd Hafis; Azizan Ashman, Muhammad Ashman Hakimi; Ibrahim, Muhammad Shuhaimi; Mohd Jamir, Mohd Ridzuan (Malaysian Tribology Society, 2023)
Water-based lubricants offer cost-effective benefits and are safer for both the environment and human personnel compared to oil-based lubricants. In this study, ceramic-based nanoparticles, namely MgO and SiC, were investigated as nanoadditives to enhance the performance of water-based lubrication. The methodology involved formulating the nanoparticles in water-based lubricants and characterizing the sedimentation, physical, mechanical, thermal, and tribological properties. The results demonstrated that the dispersion stability of the lubricants improved when mixed with Glycerol and Polyvinylpyrrolidone. The comparison between MgO and SiC nanoparticles in water-based lubrication revealed enhancements in viscosity, friction, wear, and thermal properties. This improvement was further validated through FESEM-EDS analysis, which revealed a reduction in friction and wear owing to the ball-bearing effect and the formation of a protective film. Moreover, the study highlighted the deposition of nanoparticles on the contact surfaces, which not only facilitated the mending effect but also played a significant role in reducing surface roughness by acting as a polishing agent.